1974
DOI: 10.1577/1548-8659(1974)103<336:prohrm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Hatchery Reared Muskellunge (Esox masquinongy) to Handling

Abstract: Increases in plasma lactate and glucose concentrations, along with decreases in plasma chloride and liver glycogen concentrations, were observed in muskellunge in response to capture and handling. Holding muskellunge in 0.3% NaCl alleviated some of the physiological symptoms of stress, but holding the fish in the lake for 48 hr before release had no effect. Physiological responses to fin‐clipping and transport by truck were slight in comparison to that of original capture. Salt treatment and reduction in durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
1
4

Year Published

1980
1980
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
5
16
1
4
Order By: Relevance
“…Hyperglycemia is associated with stressful situations (Wedemeyer 1972;Fletcher 1975) and bacterial infections (Herbell et al 1979), while hypoglycemia may accompany intensive physical effort (Blac et al 1966;Miles et al 1974;Driedzic and Kiceniuk 1976). The present study revealed, that in the case of glucose deltametrin solution caused statistically significant decrease of the level of this compound in the blood serum only in spring, following 48-h exposure of the fish (Tab.…”
Section: Resultssupporting
confidence: 52%
“…Hyperglycemia is associated with stressful situations (Wedemeyer 1972;Fletcher 1975) and bacterial infections (Herbell et al 1979), while hypoglycemia may accompany intensive physical effort (Blac et al 1966;Miles et al 1974;Driedzic and Kiceniuk 1976). The present study revealed, that in the case of glucose deltametrin solution caused statistically significant decrease of the level of this compound in the blood serum only in spring, following 48-h exposure of the fish (Tab.…”
Section: Resultssupporting
confidence: 52%
“…The gathering and loading procedures preceding slaughter are associated with netting, handling, crowding, changes of environment and sometimes with a temporary extraction from the water or changes in water quality and are stressful for fish (Miles et al, 1974;Specker and Schreck, 1980;Cnaani et al, 2004). Handling and confinement induced increased secretion of adrenaline and corticosteroids in the salmon, while struggling and hypoxia resulted in increases in the plasma corticosteroids.…”
Section: Farmed Fishmentioning
confidence: 99%
“…Barnhart (6) showed that diet, strain, and age affected hematological characteristics of rainbow trout (Salmo gairdneri). Also, the stress of handling, anesthesia, and various methods of capture significantly altered blood characteristics in salmonids (7)(8)(9). These studies illustrated that normal or baseline concentrations of hematological and tissue constituents in fish are difficult to determine and are a major obstacle facing the aquatic toxicologist attempting to develop diagnostic tests.…”
mentioning
confidence: 99%